PENGARUH KECUKUPAN MODAL, LIKUIDITAS, DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS PADA LPD DI KOTA DENPASAR - Krisnia Putri, I Gst Ayu Nyoman; Mustanda, I Ketut (E-Jurnal Manajemen; Vol 8 No 6 (2019), 2019)
The purpose of this study was to determine the effect of Capital Adequacy, Liquidity, and Non-Performing Loans on Profitability. This research was conducted at Village Credit Institutions in Denpasar City for the period 2015 to 2017. The number of samples used was 35 LPDs. with saturated sampling method. The data collection method used is the non-participant observation method, namely through observations made on the publication documents of LPD financial report data. Type of data is Quantitative data. The data source used is secondary data. The analysis technique used is multiple linear regression. This study proves that Capital Adequacy and Liquidity have a positive and significant effect on Profitability. This shows that Capital Adequacy and Liquidity affect the increase or increase in profitability, while Non Performing Loans have a negative and significant effect on profitability, this indicates that if there is an increase in Non Performing Loans then Profitability has decreased. Keywords : capital adequacy, liquidity, NPL, profitability